1995
DOI: 10.1093/clinids/21.2.352
|View full text |Cite
|
Sign up to set email alerts
|

Neuroretinitis, Aseptic Meningitis, and Lymphadenitis Associated with Bartonella (Rochalimaea) henselae Infection in Immunocompetent Patients and Patients Infected with Human Immunodeficiency Virus Type 1

Abstract: Bartonella (Rochalimaea) henselae causes a variety of diseases, including bacillary angiomatosis, peliosis hepatis, lymphadenitis, aseptic meningitis with bacteremia, and cat-scratch disease (CSD). Cases of B. henselae-related disease were collected from September 1991 through November 1993. Patients with suspected CSD, unexplained fever and lymphadenitis, or suspected B. henselae infection who were seen in the Infectious Diseases Clinic at Wilford Hall Medical Center (Lackland Air Force Base, TX) underwent ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
5

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(71 citation statements)
references
References 21 publications
2
64
0
5
Order By: Relevance
“…[3][4][5] Disseminated CSD may involve the eye and cause vision-threatening manifestations, including neuroretinitis, optic neuritis, retinitis, choroiditis, anterior uveitis, vitritis, branch retinal arteriolar and venular occlusions, vasculitis, and peripapillary angiomatosis. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In 1970, Sweeney and Drance 22 were first to find a connection between CSD and the appearance of neuroretinitis. Since then, numerous reports had been published on cases of neuroretinitis in CSD and it is the most common posterior segment complication of CSD.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Disseminated CSD may involve the eye and cause vision-threatening manifestations, including neuroretinitis, optic neuritis, retinitis, choroiditis, anterior uveitis, vitritis, branch retinal arteriolar and venular occlusions, vasculitis, and peripapillary angiomatosis. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In 1970, Sweeney and Drance 22 were first to find a connection between CSD and the appearance of neuroretinitis. Since then, numerous reports had been published on cases of neuroretinitis in CSD and it is the most common posterior segment complication of CSD.…”
Section: Introductionmentioning
confidence: 99%
“…Other less common syndromes associated with B. henselae occur mainly in irnmunocompromised people, and include the vasculoproliferative disease bacillary angiomatosis (BA) (18,19,21,24,27,28,30,31), bacillary peliosis (29,33), endocarditis (15), and other syndromes (34). CSD varies in severity from a benign, self-limiting disease to a severe disseminated disease which may require hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…A syndrome of aseptic meningitis is rarely described and we have found three cases in the literature, one reported by Lucey et al in immunocompetent patient whose CSF analysis revealed 19 leukocytes/mm 3 (100% mononuclear), a protein level of 62 mg/dL, and a glucose level of 76 mg/dL [1]. The other two cases were reported by Wong et al one in HIV-positive patient [2]. These findings are compatible with the alterations encountered in our patient and probably could be more often than is currently diagnosed.…”
Section: Discussionmentioning
confidence: 60%
“…So far only three cases have been described in the literature, two of them in patients with HIV infection [1,2]. We report a case of aseptic meningitis in a previously healthy patient, HIV negative, who also had visual loss due to neuroretinitis, a far more common complication of CSD.…”
mentioning
confidence: 89%